Azathioprine-induced fever in autoimmune hepatitis - Khoury, Tawfik (Baishideng Publishing Group Co., Limited, 2013)
Underdiagnosis of drug-induced fever leads to extensive investigation and prolongation of hospitalization, and may lead to multiple unnecessary invasive procedures and a wrong diagnosis. Azathioprine is a widely used immunosuppressive drug. We report a case of a 53-year-old female patient diagnosed with autoimmune hepatitis treated with azathioprine, who presented to the emergency room with a 6-wk history of fever and chills without other associated symptoms. Since the patient’s fever was of unknown origin, she was hospitalized. All treatment was stopped and an extensive workup to explore the source of fever and chills was performed. Results of chest X-ray, viral, urine, and blood cultures, autoimmune serology, transthoracic and transesophageal echocardiography, and abdominal ultrasound revealed no source of infection. A rechallenge test of azathioprine was performed and the fever and chills returned within a few hours. Azathioprine was established as the definite cause following rechallenge. Fever as an adverse drug reaction is often unrecognized. Azathioprine has been reported to cause drug-induced fever in patients with inflammatory bowel disease, rheumatoid arthritis, and sarcoidosis. To the best of our knowledge there have been no previous reports documenting azathioprine-induced fever in patients with autoimmune hepatitis. The occurrence of fever following the readministration of azathioprine suggests the diagnosis of drug-induced fever, particularly after the exclusion of other causes. A careful rechallenge is recommended to confirm the diagnosis.